Using GIS and optimization to manage construction and demolition waste: The case of abandoned quarries in Lebanon - AlZaghrini, Nadine (2019)
Increased stress on raw material and limited landfill space due to increasing rates of urbanization have encouraged efforts to divert Construction and Demolition Waste (C&DW) away from landfills toward sorting, recycling, and reusing. While these efforts have been successful in some countries (e.g., Germany, Netherlands), developing countries tend to suffer from illegal and haphazard dumping of C&DW. This study presents an optimization based decision support tool to select a cost and environmentally effective set of abandoned quarries to serve as C&DW landfills and processing facilities. The tool is composed of a GIS model and a mixed integer linear program that accounts for the complete waste management chain. A case study in Lebanon served as a testbed for the tool: A multi-criteria analysis was first used in GIS to evaluate the environmental suitability of candidate quarries based on five thematic groups: socio-economic, topography, geology, hydrology and infrastructure. The most suitable quarries were then inputted to the optimization model. Two out of 148 abandoned quarries in Mount Lebanon were deemed suitable for rehabilitation under the objectives set yielding a profit of 125 million US dollars over a 20 year span. Future challenges include enhancing the model by incorporating time and accounting for more recycling technologies.